2008
DOI: 10.4103/0255-0857.42037
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pheromone response in biofilm forming clinical isolates of high level gentamicin resistant <i> Enterococcus faecalis</i>

Abstract: Twenty Þ ve clinical isolates of high level gentamicin resistant Enterococcus faecalis were tested for their bioÞ lm formation and pheromone responsiveness. The bioÞ lm assay was carried out using microtiter plate method. Two isolates out of the 25 (8%) were high bioÞ lm formers and 19 (76%) and four (16%) isolates were moderate and weak bioÞ lm formers respectively. All the isolates responded to pheromones of E. faecalis FA2-2 strain. On addition of pheromone producing E. faecalis FA2-2 strain to these isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Acinetobacter , Pseudomonas, Klebsiella, Staphylococcus, Enterobacter, and E. coli are the most common causes of nosocomial infections, and that may be common cause of colonization in indwelling medical devices even responsible for biofilm production [10, 11]. These microorganisms survive in hospital environments despite unfavorable conditions such as desiccation, nutrient starvation, and antimicrobial treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acinetobacter , Pseudomonas, Klebsiella, Staphylococcus, Enterobacter, and E. coli are the most common causes of nosocomial infections, and that may be common cause of colonization in indwelling medical devices even responsible for biofilm production [10, 11]. These microorganisms survive in hospital environments despite unfavorable conditions such as desiccation, nutrient starvation, and antimicrobial treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Donlan et al showed that the organisms most commonly isolated from central venous catheter biofilms are Staphylococcus epidermidis, S. aureus, Candida albicans, P. aeruginosa, K. pneumoniae, and Enterococcus faecalis [9, 10]. Stickler et al [17] showed that the organisms commonly contaminating this urinary catheter and developing biofilms are S. epidermidis, Enterococcus faecalis, E. coli, Proteus mirabilis, P. aeruginosa, K. pneumoniae, and other gram-negative organisms [2, 911]. The study of different mechanisms of drug resistance showed isolates commonly found positive for ESBL, carbapenemase production in gram-negative organism and MRSA, vancomycin resistance among gram-positive organisms.…”
Section: Discussionmentioning
confidence: 99%
“…These isolated strains were considered clinically significant when obtained in pure culture from the clinical samples or in significant numbers as part of mixed cultures. The isolates were further identified in accordance with the standard procedure [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…The possession of diverse virulence factors has been an important benefit for enterococci, since possessing any of them may change the severity of infections caused by these bacteria. On the other hand, it is believed that nosocomial enterococci might have virulence elements that increase their ability to colonize hospitalized patients [ 4 , 8 , 9 ]. Resolution of the high level gentamicin resistant enterococci infections is further complicated by the presence of virulence factors present in these organisms [ 9 ].…”
Section: Introductionmentioning
confidence: 99%